The Power of Political Déjà Vu: When Collective Action Becomes an Effort to Change the Future by Preventing the Return of the Past. Issue 2 (6th November 2020) - Chayinska, Maria; McGarty, Craig
Abstract : This article examines the conditions under which political déjà vu (PDV), a perceived analogy between past and present societal‐level traumatic events, can mobilize people to support system‐changing collective action. We propose that individuals' perceptions of PDV can evolve both social identification with a group that sustains the victimized and disidentification with the perceived perpetrators. We further suggest that disidentification and identification can form two distinct psychological paths to collective action through the sequential effects of moral outrage and collective efficacy beliefs. We tested these ideas in a cross‐sectional field study ( N  = 272) in the context of antigovernment protests over a missing activist in Argentina, a country with a legacy of enforced disappearances. The findings demonstrated that perceiving two events from different times as similar simultaneously predicted identifying as a supporter of the victimized and disidentifying with the perceived wrongdoer. Disidentification was found to predict collective action intentions through the sequential effect of collective efficacy beliefs and moral outrage, whereas the indirect effect of social identification was nonsignificant. Results provide an intriguing example of the effects of perceived PDV in social mobilization and extend our understanding of disidentification as a powerful predictor of collective action.